TAMAN REKREASI AIR DI PONTIANAK UTARA - Lunar, Flavia Tiffany; Purnomo, Yudi; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
Following the COVID-19 pandemic, public awareness of healthy lifestyles and mental health well-being has notably increased. This presents a significant opportunity to create environments that foster innovation in health and wellness, thereby supporting economic growth. However, the limited availability of integrated facilities has become a major obstacle in fulfilling the public